Genius : the game - Gout, Leopoldo (Feiwel & Friends, an imprint of Macmillan, 2016)
As 200 geniuses from around the world go head to head in a competition hand-devised by India's youngest CEO and visionary, the stakes are higher than anyone can imagine. Like life and death. Welcome to the revolution... and get ready to run.